ANALYSIS OF THE DEVELOPMENT OF HALAL CERTIFICATION IN MSMES IN WEST JAVA IN 2023: CHALLENGES AND GOVERNMENT TARGETS - Nugraha, Arinaldi; Dedi Pujakesuma (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Halal certification is an important aspect in increasing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in West Java, considering the large Muslim population in Indonesia. This study aims to analyze the development of halal certification in West Java MSMEs in 2023, identify the challenges faced, and evaluate the government's efforts and targets in supporting the acceleration of halal certification. This research approach is qualitative, with data collection techniques through in-depth interviews with the Secretary of the Halal Product Guarantee Organizing Agency (BPJPH) and supported by statistical data related to the development of halal certification. The findings show that the development of halal certification in West Java in 2023 shows significant achievements with the realization of 189,886 certificates, although it is still faced with challenges in MSME literacy, administrative obstacles, and limited BPJPH resources.